Anal Fissures in Pediatrics, and Its Non-Surgical Management, A Review Study - Alaa Mohammed Ali Al Baazi; Athir Ahmed Kadium; Mahmood Mosa Mahmood (Indian Journal of Forensic Medicine & Toxicology, 2021)
The aim of this study is to show the effect of conservative therapy in management of anal fissures in pediatrics.Study samples were patients presenting to Central Teaching Hospital of Paediatrics between Feb. 2012 to Mar.2013. In prospective descriptive-analytical study,50 cases with anal fissures were evaluated in the pediatricsurgery outpatient clinic. All cases were subjected to medical history and clinical examination. The collecteddata were classified in tables. In history we focused on dietary habits , bowel habits , rectal bleeding, painfuldefecation & constipation. The collected data consisted of age, sex, presentation & location of fissure. In clinicalexamination we assessed the site , presence of skin tags & PR if needed. All cases underwent conservativetreatment for anal fissure by using proctocidar ointment locally 2-3 times daily for 3-6 weeks & lidocaine gel2% applied 10 minutes before defecation to minimize the pain. Lactulose syrup was given 2-3 times dailywith meal to soften the stool & Purgative (Dulcolax) orally in addition to dietary habit instructions. Twopatients only not responded to this regimen , so underwent anal dilatation under general anaesthesia. In ourstudy a total of 50 cases (30 cases 60% Males & 20 cases 40% Females) at age between (6 months - 3years)presented in central teaching hospital of pediatrics mainly as pain during defecation. All were evaluated ,diagnosed & managed during the period from Feb.2012 to Mar. 2013 & followed up for 3-6 weeks. In about48 cases (96%) associated with constipation & 2 cases (4%) associated with diarrhea. 34 cases (68%) hadpain during defecation & 27 cases (54%) had bleeding per rectum (streaks of blood or small drops of blood).All Patients were diagnosed clinically by history from parents & local examination. 45 cases of fissures inano were located posteriorly, 3 were anteriorly located & only 2 cases have fissures on both sides. 48 caseshad history of developing symptoms within 2 weeks period & underwent medical management in the formof laxatives e.g. lactulose & purgatives e.g. dulcolax in addition to lidocaine gel 2% which is topicallyapplied for about 3 to 6 weeks resulting in complete healing. 2 cases (4%) only were not responded to thisregimen & needed anal dilatation. We found that an acute anal fissure is more common than chronic inpediatrics. The most common presenting symptoms were pain during defecation & constipation. Conclusion: Anal fissures can be simply and effectively treated medically by topical proctocidar ointmentand lidocaine gel 2% in addition to lactulose syrup & purgative. These are an excellent combination,associated with a low recurrence rate and minimal side effects.